Haemorrhagic mesenteric abscess in infective endocarditis: a unique cause of spontaneous haemoperitoneum. Issue 2 (2nd February 2023) - Read, Phillipa; Walker, Patrick; Menon, Tulsi
Abstract: Spontaneous haemoperitoneum (SH) is a rare but life-threatening condition with several well-recognized causes. SH often occurs in anticoagulated patients and requires urgent treatment to prevent mortality. SH is rarely associated with infective endocarditis (IE). To date, there are no reported cases of a haemorrhagic mesenteric abscess causing haemoperitoneum. We present the case of a warfarinized 30-year-old intravenous drug user with IE 2 weeks post-revision of a metallic valve who reported abdominal pain and subsequently suffered haemodynamic collapse. Abdominal computed tomography and damage-control laparotomy revealed haemoperitoneum secondary to an actively bleeding mesenteric nodule which was resected. Histopathology confirmed a haemorrhagic mesenteric abscess representing a rare sequela of IE and a novel cause of SH. Given that the incidence of IE appears to be increasing in people who inject drugs in Australia, the general surgeon should be aware of this clinical entity and the need for urgent intervention to prevent catastrophic sequelae.